Seasonal variation in hospital admission for road traffic injuries in England: analysis of hospital statistics. - Gill, M; Goldacre, M (2009)
OBJECTIVE: To report on seasonal variation in hospital admissions for traffic injuries to car and truck occupants, motorcyclists, cyclists, and pedestrians. METHODS: Descriptive study of hospital admission statistics in England, 1999-2004. MAIN OUTCOME MEASURES: national average monthly admissions for injury; severity of injury, defined as death in hospital or a hospital admission lasting four days or more. RESULTS: Admissions for car occupants were highest in the winter months but seasonal variation was not great (highest and lowest months: December, 16% above monthly average; June, 5% below). There was a summer peak and winter trough in admissions for adult cyclists (June, 34% above average; December, 27% below) and motorcyclists (August, 33% above average; January, 43% below). Admissions for child pedestrians were highest in late spring and lowest in mid-winter (May, 24% above average; December, 28% below). By contrast, admissions for adult pedestrians were higher in winter than summer (December, 33% above average; July, 17% below). From April to September, there were more admissions for pedestrians and cyclists in England (44 875 in the six years of the study) than for car occupants (34 582). For cyclists, proportionally more injuries in the winter months were severe. Severity of injuries to car occupants did not show seasonal variation. CONCLUSIONS: The public health "toll" of traffic injuries, measured as total numbers of people injured, varies substantially by season. Although it is important to reduce all injuries, the safety of pedestrians and cyclists, as unprotected road users, needs particular attention.